Development of HOTS-Based Questions as an Implementation of the Deep Learning Approach in the Merdeka Curriculum - Nurhemah, Neng; Rosmiati, Yatti; Putri, Mas Fierna Janvierna Lusie (CV. Rayyan Dwi Bharata, 2026)
The Merdeka Curriculum is designed to develop students who are adaptive, creative, critical, and reflective in facing 21st-century challenges. However, many teachers still experience difficulties in designing assessment instruments based on Higher Order Thinking Skills (HOTS), causing learning activities to focus predominantly on Lower Order Thinking Skills (LOTS). To address this issue, a community service program was implemented to enhance teachers’ understanding of HOTS and deep learning concepts, strengthen their skills in developing HOTS-based assessment questions aligned with Merdeka Curriculum learning outcomes, and encourage their integration into instructional planning. The program was conducted through socialization, counseling, interactive workshops, mentoring, and reflective evaluation, involving teachers from SMK IPTEK, South Tangerang City. The results demonstrated a significant improvement in teachers’ comprehension of HOTS and their ability to design assessment items targeting analytical, evaluative, and creative thinking skills (C4–C6). Teachers also successfully integrated digital tools such as Google Forms and Quizizz for interactive assessments. Overall, the program positively impacted learning quality and supported the realization of the Pancasila Student Profile.